2022
DOI: 10.3390/cancers14020302
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Associated with Immune-Related Adverse Events under Checkpoint Inhibitors in Metastatic Melanoma

Abstract: Immune checkpoint inhibitors (ICI) have revolutionized the therapeutic landscape of metastatic melanoma. However, ICI are often associated with immune-related adverse events (IRAE) such as colitis, hepatitis, pancreatitis, hypophysitis, pneumonitis, thyroiditis, exanthema, nephritis, myositis, encephalitis, or myocarditis. Biomarkers associated with the occurrence of IRAE would be desirable. In the literature, there is only little data available and furthermore mostly speculative, especially in view of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…One study found an association between increased leukocytes and absolute number of neutrophils at the start of immunotherapy with the occurrence of irAEs. Additionally, there was also an association with HLA-I and HLA-A homozygosity and the occurrence of irAEs [12 ▪ ].…”
Section: Introductionmentioning
confidence: 91%
“…One study found an association between increased leukocytes and absolute number of neutrophils at the start of immunotherapy with the occurrence of irAEs. Additionally, there was also an association with HLA-I and HLA-A homozygosity and the occurrence of irAEs [12 ▪ ].…”
Section: Introductionmentioning
confidence: 91%
“…Studies have demonstrated that combination therapy with anti-PD-1 and anti-CTLA4 poses a higher risk of frequency and severity of irAEs compared with monotherapy. Melanoma and genitourinary cancers appear to confer an increased risk of irAEs, which is highly suggestive of the role of tumor biology in the development of drug-related toxicity [8][9][10]11 ICI-PI is infrequent, and hence knowledge of its biological and physiopathological aspects is limited. A vast majority of patients with ICI-PI present with an asymptomatic elevation of pancreatic enzymes.…”
Section: Andandmentioning
confidence: 99%
“…]. Caucasian men in the sixth decade of life with advanced stage of cancer are at higher risk of developing irAEs [10,12].…”
Section: Abstract Autoimmune Pancreatitis Diagnosis and Management Of...mentioning
confidence: 99%
See 2 more Smart Citations